2020
DOI: 10.17969/jimfp.v4i1.10360
|View full text |Cite
|
Sign up to set email alerts
|

Perubahan Beberapa Sifat Fisika Gambut Akibat Lamanya Penggunaan Lahan di Rawa Tripa

Abstract: Abstrak. Histosol merupakan tanah organik yang terbentuk dari kumpulan bahan-bahan organik seperti serasah tumbuhan yang terdekomposisi dalam jangka waktu yang lama. Di Aceh sendiri wilayah ekosistem rawa gambut yang telah dikonversi menjadi lahan pertanian dan perkebunan adalah wilayah barat mulai dari Kabupaten Aceh Jaya hingga Kabupaten Aceh Singkil. Penelitian ini bertujuan untuk melihat perubahan beberapa sifat fisika dan kimia gambut akibat lamanya penggunaan lahan di Rawa Tripa Kabupaten Nagan Raya.Hasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…In Central Kalimantan and West Kalimantan, the difference in Corganic contained in various types of peat land uses seems to be influenced by the kind of commodity and the time it has been managed. The results of this study agree with the findings of Devi et al (2019), who found that the maturity level of peat soil is strongly related to the length of time the peatland has been used, and the degree of maturity of the peat is related to bulk density. Similar types of findings have been reported by Adji (2017).…”
Section: Carbon Contentsupporting
confidence: 92%
“…In Central Kalimantan and West Kalimantan, the difference in Corganic contained in various types of peat land uses seems to be influenced by the kind of commodity and the time it has been managed. The results of this study agree with the findings of Devi et al (2019), who found that the maturity level of peat soil is strongly related to the length of time the peatland has been used, and the degree of maturity of the peat is related to bulk density. Similar types of findings have been reported by Adji (2017).…”
Section: Carbon Contentsupporting
confidence: 92%
“…Peatlands that are good for agriculture and plantations are peat soils whose maturity level is already 3 at the sapric level or has matured. [9] Figure 2. Soil map of Rangang Island…”
Section: Peatlands In Rangsang Islandsmentioning
confidence: 99%